Evaluación de la calidad de servicio en el área de obstetricia del Sub-Centro de Salud de la Parroquia Quiroga Cantón Bolívar - Almeida Vélez, María Gabriela (2018)
This research was carried out at the sub-center of Health of the Quiroga parish of Bolívar canton. Its main objective was to evaluate the service quality in the Obstetrics area, therefore, to improve the expectations that users have of the care provided. It was developed through three stages: In the first, the services provided by the area were identified, the necessary permission was required through an official letter addressed to the District Director of the Ministry of Public Health, and to the Director of the Quiroga Health sub-center, for the respective permission of the thesis development, and thus achieve the corresponding interview with the Director in charge since he knows each of the needs of the obstetrics area and especially the lack of an obstetrician. In the second stage, the application of the user survey was given through the SERVQUAL method, an instrument that measures quality in five dimensions: reliability, responsiveness, security, empathy and tangible elements, allowing the appreciation of each feature of the evaluated service of the Quiroga Sub-Center. In the third stage, the proposal was proposed through an improvement plan for the Obstetrics area, establishing strategies, actions and possible solutions that the institution should promote in order to achieve excellence satisfaction towards the users.